The Role of Forensic Linguistics and Case Studies, Demonstrating the Effectiveness of Linguists’ Contribution to the Investigations - Ürmösné Simon, Gabriella; Kudar, Mariann (Magyar Rendészet, 2025)
This paper explores the multifaceted role of forensic linguistics in which linguists have assisted in the investigation of crime authorities. The purpose of the study is to represent the role of forensic linguist in the detection of crimes, and it also covers the investigation of methods and authorship, as well as the identity and affiliation of the perpetrator. Using a prescriptive method, the study explores the task and work of forensic linguists and forensic text linguistics, and also illustrates the methods of forensic linguists through four case studies, with the help of which the linguists tried to wrap up two cases. The study demonstrates that in many cases it is essential to involve a forensic linguist in certain investigative phases, even in relation to certain cases, such as voice recordings or written texts (suicide notes, blackmail letters, text messages). The mentioned cases clearly testify the extent to which linguists can play a role when an investigation stalls at a certain point, and the authorities need authorship investigation, voice recognition, the discovery of linguistic evidence, text analysis, comparison with other texts and the profiling of the perpetrator.